2020
DOI: 10.1186/s13662-020-2500-y
|View full text |Cite
|
Sign up to set email alerts
|

A new class of travelling wave solutions for local fractional diffusion differential equations

Abstract: In this paper, we investigate a 3-D diffusion equation within the scope of the local fractional derivative. For this model, we establish local fractional vector operators and a local fractional Laplace operator defined on Cantor-type cylindrical coordinate and Cantor-type spherical coordinate, respectively. With the help of the spherical symmetry method based on those operators, we obtain exact traveling wave solutions of the 3-D diffusion equation. The results reveal that the proposed schemes are very effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In a similar way, substituting Equations (36) and (37) into Equation (42), we obtain the local fractional quaternionic Helmholtz equation in the Cantor-type spherical coordinates.…”
Section: The Cantor-type Cylindrical and Spherical-coordinate Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a similar way, substituting Equations (36) and (37) into Equation (42), we obtain the local fractional quaternionic Helmholtz equation in the Cantor-type spherical coordinates.…”
Section: The Cantor-type Cylindrical and Spherical-coordinate Methodsmentioning
confidence: 99%
“…We begin our study by recalling some facts on local fractional calculus that can be found in other studies. 36,41 Definition 1. Let f(x) be a function defined on a fractal set of fractal dimension (0 < < 1); the function f(x) is said to be local fractional continuous at x = x 0 if for each > 0, there exists a corresponding > 0 such that…”
Section: Few Aspects Of Local Fractional Calculusmentioning
confidence: 99%
See 3 more Smart Citations